Factor V Leiden Mutation and Neonatal Stroke - J Gordon Millichap (Pediatric Neurology Briefs)
Three infants with familial factor V Leiden mutation and neonatal cerebrovascular disorders are reported from the Children’s Hospital of Philadelphia, PA.